Qualidade nutricional e valor protéico da amêndoa de baru em relação ao amendoim, castanha-de-caju e castanha-do-pará - Freitas, Jullyana Borges de (2009)
The aim of this study was to characterize the chemical composition of the roasted baru almond, which is derived from different native plants in the west of the State of Goiás, and to compare its protein quality to that of the peanut, cashew nut and Brazil nut. Standardized methods were used to determine centesimal composition, amino acid profile, fatty acids and mineral content. The experiment was carried out with 42 male weanling Wistar rats. The animals were randomly assigned into seven groups. The experiment lasted fourteen days. The diets were formulated according to AIN-93G, six diets with 10% protein: CAS7 (7% lipid casein), CAS15 (15% lipid casein), BA (baru almond), PN (peanut), CN (cashew nut), BN (Brazil nut) and a protein-free diet. The consumption was controlled according to the energy value of the diets. The protein value was estimated using NPR (Net Protein Ratio) and PDCAAS (Protein Digestibility-Corrected Amino Acid Score). The seeds and nuts are sources of proteins (16.3 to 32.3g.100g-1) and lipids (42.7 to 57.9g.100g-1). The protein content of baru almonds varied significantly (Tukey, p<0.05) between plants (24.2 to 31.9g.100g-1). The amino acid profile of baru almonds also varied significantly between plants. Lysine (Limiting Essential Amino Acid - LEAA of 43% to 72%) and sulfur amino acids (LEAA of 78% to 90%) were the limiting amino acids, according to the WHO/FAO/UNU standard for school children. The best 6: 3 fatty acid ratio (9: 1) was found in the baru almond, which is rich in iron (3.6 to 4.7mg.100g-1) and zinc (2.8 to 4.1mg.100g-1). The cashew nut had a relative NPR of 81%, followed by the Brazil nut (68%), peanut (61%) and baru almond (45%). The PDCAAS varied significantly between baru plants (32% to 68%), and between the other samples (63% for the BN, 69% for the PN and 88% for CN). There are differences in the nutritional value of baru almonds from different plants in the same Cerrado subpopulation and between different seeds and nuts. These foods present a high density of nutrients such as proteins, lipids, minerals and dietary fiber. For this reason, their inclusion in the diet and use in home and industrial food processing should be encouraged.